2014
DOI: 10.15171/ijhpm.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

Household financial contribution to the health System in Shiraz, Iran in 2012

Abstract: It appears that the current method of health financing in Iran does not adequately protect households against catastrophic health expenditure. Consequently, it is essential to reform healthcare financing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
58
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 19 publications
7
58
3
2
Order By: Relevance
“…Thus, the households not covered by supplementary insurance or those taking services not included in the package of basic insurance companies (eg, dental care services) would allocate a higher percentage of their capacity to pay to health expenditures; studies in Iran and other countries have also confirmed this hypothesis. 11,19,31 In this study, no relationship was found between household size and the chances of facing CHE. Similarly, in 2012, Kavosi et al found no such a relationship.…”
Section: 19contrasting
confidence: 58%
See 4 more Smart Citations
“…Thus, the households not covered by supplementary insurance or those taking services not included in the package of basic insurance companies (eg, dental care services) would allocate a higher percentage of their capacity to pay to health expenditures; studies in Iran and other countries have also confirmed this hypothesis. 11,19,31 In this study, no relationship was found between household size and the chances of facing CHE. Similarly, in 2012, Kavosi et al found no such a relationship.…”
Section: 19contrasting
confidence: 58%
“…The study conducted by Kavosi et al in 2014 revealed that for every instance of taking outpatient services, the probability of facing CHE would increase by 11%. 19 Nevertheless, Amery et al, in their 2013 study, concluded that there was no significant relationship between receiving outpatient services and CHE. 18 The results of our study also showed no significant relationship between having basic health insurance and the risk of exposure to CHE.…”
Section: 19mentioning
confidence: 98%
See 3 more Smart Citations